National and International in Vasyl Mysyk’s Poetry - Калашник, Володимир Семенович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is an attempt to comprehend and evaluate scientific achievements of the prominent Ukrainian linguist V. V. Akulenko whose activity was connected with Kharkiv University for a long time. On the basis of the scientist’s conception about the importance of international elements in world languages, national signs of V. Mysyk’s poetry language form are considered in their unity with the adopted from foreign sources, primarily from the cultures of European and Eastern peoples. On the background of the means of creating national colour, a number of intertextemes are characterized, their aesthetic functions are emphasised. A conclusion is made about enriching Ukrainian linguistic world image by the international elements used in V. Mysyk’s lyrics.